1983
DOI: 10.1111/j.1471-4159.1983.tb04767.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Localization of Gangliosides in the Developing Mouse Cerebellum: Analysis Using the Weaver Mutant

Abstract: The distribution of gangliosides was studied in the weaver (wv/wv) mutant mouse, where the vast majority of postmitotic granule cell neurons die prior to their differentiation. The wv mutation also shows a dosage effect, as granule cell migration is slowed or retarded in the +/wv heterozygotes. By correlating changes in ganglioside composition with the well-documented histological events that occur during cerebellar development in the normal (+/+), heterozygous (+/wv), and weaver (wv/wv) mutant mice, informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1

Year Published

1985
1985
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 73 publications
6
51
1
Order By: Relevance
“…In contrast to the C-BS, where GM1 is a major ganglioside, GM1 was a minor ganglioside in the cerebellum of normal B6 mice at p-15 (Table 2). This is consistent with previous observations in normal mice (29,47). However, GM1 was ‫-4ف‬fold greater in the C-BS and ‫-5ف‬ fold greater in the cerebellum of the untreated ␤-gal Ϫ/Ϫ mice than in the untreated B6 mice (Table 2).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast to the C-BS, where GM1 is a major ganglioside, GM1 was a minor ganglioside in the cerebellum of normal B6 mice at p-15 (Table 2). This is consistent with previous observations in normal mice (29,47). However, GM1 was ‫-4ف‬fold greater in the C-BS and ‫-5ف‬ fold greater in the cerebellum of the untreated ␤-gal Ϫ/Ϫ mice than in the untreated B6 mice (Table 2).…”
Section: Resultssupporting
confidence: 93%
“…GD3 is enriched in vertebrate CNS neuroectodermal cells, including granule cells of the EGL, in the developing mouse cerebellum (29,(47)(48)(49)(50)(51)(52)(53). Our findings indicate that inhibition of total ganglioside and GD3 biosynthesis did not affect the migration of granule cells from the EGL to the internal granular layer.…”
Section: Discussionmentioning
confidence: 60%
“…Studies using mouse neurological mutants have suggested that G D~ is concentrated in undifferentiated granule cell neurons of the cerebellum and also in reactive astrocytes [Seyfried et al, 1983. Immunocytochemical studies using two different monoclonal antibodies against GD3 have confirmed and extended these biochemical studies [Goldman et al, 1984;Curtis et al, 19881.…”
Section: Introductionmentioning
confidence: 86%
“…A significant body of literature suggests that gangliosides are expressed in the CNS in a cellspecific and developmentally regulated fashion (Ledeen, 1985;Yu, 1993). Furthermore, changes in GSL expression during development correlate with changes in cellular growth and migration, differentiation, neuritogenesis, and synaptogenesis (Suzuki, 1965;Irwin et al, 1980;Seyfried et al, 1983;Bremer et al, 1986;Fenderson et al, 1987;Andrews et al, 1990;Hakomori, 1990;Schengrund, 1990;Rosenberg et al, 1992;Rosenberg and Noble, 1993;Wu et al, 1995;Zeng et al, 1995). These findings, together with evidence for a phylogenetic conservation of ganglioside expression and the absence of natural ganglioside biosynthetic mutations, have led to the hypothesis that GSLs play a critical role in developmental processes (Seyfried, 1988;Irvine and Seyfried, 1994).…”
mentioning
confidence: 99%